Answer:
3 1/2 miles
Step-by-step explanation:
because 6 - 2 1/2 = 3 1/2
Answer:
I am pretty sure it's A, 85% sure
Step-by-step explanation:
Sorry wasn't a ton of help, ignore if there is a better answer but you seem like in a rush
Answer:
12565.11 teeth approximately cut cross the cutting surface per seconds.
Step-by-step explanation:
Since the diameter is 10inches, the circumference of the arm saw is 10π (circumference is πd where d is diameter).
The number of teeth on the cutting blade can be gotten by multiplying the diameter by 12 since we have 12 teeth per inch on the arm saw
Number of teeth on saw = 12 x 10π = 120π.
To get the number of teeth that cross the cutting surface in 2000rpm we multiple it by the total number of teeth in just one rpm.
So we have 2000 x 120π. But since we are asked to find it in revolution per seconds then 2000r/m = 2000r/60s ≈ 33.33
Therefore, we have
33.33 x 120π ≈ 12565.11 teeth
Problem 11
Answer: Angle C and angle F
Explanation: Angle C and the 80 degree angle are vertical angles. Vertical angles are always congruent. Angle F is equal to angle C because they are alternate interior angles.
============================================
Problem 12
Answer: 100 degrees
Explanation: Solve the equation E+F = 180, where F = 80 found earlier above. You should get E = 100.
============================================
Problem 13
Answer: 80 degrees
Explanation: This was mentioned earlier in problem 11.
============================================
Problem 14
Answers: complement = 50, supplement = 140
Explanation: Complementary angles always add to 90. Supplementary angles always add to 180. An example of supplementary angles are angles E and F forming a straight line angle.
Factor:
3x^2 + 27
= 3(x^2 + 9)
Answer is 3(x^2 + 9), when factored.
A) (3x + 9i)(x + 3i)
= (3x + 9i)(x + 3i)
= (3x)(x) + (3x)(3i) + (9i)(x) + (9i)(3i)
= 3x^2 + 9ix + 9ix + 27i^2
= 27i^2 + 18ix + 3x^2
B) (3x - 9i)(x + 3i)
= (3x + - 9i)(x + 3i)
= (3x)(x) + (3x)(3i) + ( - 9i)(x) + (- 9i)(3i)
= 3x^2 + 9ix - 9ix - 27i^2
= 27i^2 + 3x^2
C) (3x - 6i)(x + 21i)
= (3x + - 6i)(x + 21i)
= (3x)(x) + (3x)(21i) + (- 6i)(x) + ( -6i)(21i)
= 3x^2 + 63ix - 6ix - 126i^2
= - 126i^2 + 57ix + 3x^2
D) (3x - 9i)(x - 3i)
= (3x + - 9)(x + - 3)
= (3x)(x) + (3x)( - 3i) + (- 9)(x) + ( - 9)( - 3i)
= 3x^2 - 9ix - 9x + 27i
= 9ix + 3x^2 + 27i - 9x
Hope that helps!!!